Preparation of ZnO Nanoparticles by the Chemical Precipitation Method - Nuha B Kudaer; Emad Yousif; Mohseen H Risan; Mohammed Khadom (Fakultas Teknik, 2022)
In the current work, a simple method to prepare ZnO nanoparticles (NPs) by the interaction of zinc nitrate and KOH within an aqueous medium was presented. The yielded powder was calcined and examined by the UV-Visible (UV–Vis) optical absorption, Fourier Transform Infrared (FTIR) spectroscopy, Energy Dispersive X-Ray (EDX) Spectroscopy, atomic force microscopy (AFM) images, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The ZnO NPs showed an identification peak at nearly 372 nm during the FTIR test. Furthermore, when the particle size distribution was examined, it showed an average value of 27.34 nm.